Changing directions of the British welfare state - Calder, Gideon, 1971-; Gass, Jeremy; Merrill-Glover, Kirsten (University of Wales Press, 2012)
A unique and timely survey, by prominent academics and social campaigners, of the evolving priorities of the British welfare state, and the values which have underpinned it.